Curcumin supplementation in pediatric patients: A systematic review of current clinical evidence. (14th December 2021) - Heidari, Zinat; Daei, Maryam; Boozari, Motahareh; Jamialahmadi, Tannaz; Sahebkar, Amirhossein
Abstract: This systematic review was designed to determine the clinical efficacy and safety of curcumin supplementation for pediatric patients based on clinical trials in children. We systematically searched electronic databases including PubMed, EMBASE, Web of Science, and Scopus for all studies that investigated curcumin administration in the pediatric population without any time frame limitation. Finally, we identified 16 studies for this review. Clinical efficacy and safety of curcumin were assessed in children with inflammatory and immune disorders (including asthma, inflammatory bowel disease (IBD), and juvenile idiopathic arthritis (JIA)), metabolic disorders, autosomal dominant polycystic kidney disease (ADPKD), cystic fibrosis (CF), tetralogy of Fallot (TOF), and infectious diseases. Curcumin was administered in a wide range of doses (45 mg–4, 000 mg daily) and durations (2–48 weeks). Overall, curcumin was well tolerated in all studies and improved the severity of inflammatory and immune disorders and metabolic diseases. However, more studies are needed to clarify the role of curcumin supplementation among children with ADPKD, CF, TOF, and infectious diseases. Because of substantial heterogeneity in methodological quality, design, outcomes, dose, duration of intake, formulations, and study populations across studies, no quantitative analysis was performed. Additional large‐scale, randomized, placebo‐controlled clinical trials are needed to confirm the results of the conducted studies.